Interrelations between factors related to physical activity in inactive adults with knee pain. Issue 15 (17th July 2022) - Shah, Nirali; Kramer, Jessica; Borrelli, Belinda; Kumar, Deepak
Abstract: Purpose: The purpose was to explore interrelations between factors related to engagement in physical activity in inactive adults with knee pain. Method: Inactive adults with knee pain ( n  = 35) participated in six focus groups designed to inquire about barriers and facilitators related with engagement in physical activity. Directed content analysis and inductive thematic analysis were used to identify factors related to physical activity and associated interrelations respectively. As an exploratory analysis, sex differences in barriers and facilitators to physical activity were assessed. Results: In this cohort (age = 60.9 ± 8.6 years; 22 females), self-reported physical activity was 26.3 ± 46.8 min/week. Factors related to physical activity were grouped into domains of physical status, psychological status, environment, knowledge, and resources. It was seen that the interrelations between a person and their environment, as well as, between impairments and everyday responsibilities influenced engagement in physical activity. Females were more likely to identify physical and psychological status, social expectations, and lack of knowledge as barriers. Males indicated a preference for using mobile technologies to overcome barriers. Conclusion: Interplay of various barriers and facilitators is related to engagement in physical activity in inactive older adults with knee pain. Interventions to promote physical activity should address these interrelations and sex differences. Implications for rehabilitation: Interrelations between individual factors related to engagement in physical activity and sex differences in these factors are present in inactive adults with knee pain. Interventions to improve physical activity should be implemented by addressing factors and interrelations between factors related to physical activity in inactive adults with knee pain. Interventions to address low levels of physical activity in adults with knee pain should take into account sex differences.